ヒガシ ナンキョク リュツォ・ホルムワン チイキ ニ オケル カハンガタ コウタイイキ ジシンケイ ヲ モチイタ ヤガイ ジシン カンソク - 根岸, 弘明; ネギシ, ヒロアキ; 金尾, 政紀; カナオ, マサキ; Negishi, Hiroaki; Kanao, Masaki (1998)
P(論文) 第37次および第38次日本南極地域観測隊(1996-1997年)により, 東南極リュツォ・ホルム湾域の5カ所において野外地震観測が行われた。地震観測システムは可搬型広帯域地震計, 光磁気ディスクによる記録計および太陽電池による電源供給装置からなる。電源供給装置のトラブルがあった他は観測は順調に行われ, いくつかの遠地地震が観測された。周波数解析から, これら野外観測のデータは0.5Hzより高周波側で振幅が非常に大きい事が確認された。一方, 5mHzから0.5Hzの範囲では昭和基地での記録とほぼ同じレベルであり, 適切なフィルター処理をすることにより, これら野外観測のデータが様々な波形解析に活用でき得る事がわかった。 Field seismological observations were carried out at five points around the Lutzow-Holm Bay region in East Antarctica to clarify the heterogeneous structure of the crust and the upper mantle during the 37th Japanese Antarctic Research Expedition (JARE-37) and JARE-38 in 1996-97. The seismological recording system is composed of a portable broadband seismometer, a recording unit with MO disk drive and a solar power battery supply. Expect for power supply trouble, the observations went well and waveforms of some teleseismic events were recorded. Based on spectral analysis, the spectrum amplitude of the field observation data is very large at frequency higher than about 0.5Hz. On the other hand, the amplitude is almost the same as that at Syowa Station at frequencies from about 5mHz to 0.5Hz. These data are of good enough quality to be used for various waveform analyses by applying suitable band pass filters. departmental bulletin paper